Rural Women's Leadership in Atlantic Canada : First-hand Perspectives on Local Public Life and Participation in Electoral Politics - Carbert, Louise I. (Louise Irene), 1960- (Book collections on Project MUSE., 2006)
"Rural Women's Leadership in Atlantic Canada presents results from a regional field-based study, the first of its kind. In the course of her study, Louise Carbert gathered together small groups of rural community leaders (126 women in all) throughout the four Atlantic provinces, and interviewed them about their experiences and perceptions of leadership, public life, and running for elected office. Their responses paint a vivid picture of politics in rural communities, illustrating how it intersects with family life, work, and the overall local economy. Through discussion of their own reluctance to entering politics, and of the resistance encountered by those who have put their names forward, the interviewees shed much-needed light on the pervasive barriers to the election of women. Carbert not only contextualizes the results in terms of economic and demographic structures of rural Atlantic Canada, but also considers points of comparison and contrast with other parts of the country."--Jacket.